INTEGRATED WATER MANAGEMENT AND DURABILITY OF LANDSCAPE OF PUBLIC IRRIGATED AREAS IN TUNISIA: CASES OF PUBLIC IRRIGATED AREAS OF CHOTT-MARIEM AND MORNAG - Hamrita, Abdelkarim; Boussetta, Amira; Olmo, Rafael Mata; Saqalli, Mehdi; Rejeb, Hichem (International Journal of Research -GRANTHAALAYAH, 2017)
An important part of the landscape of irrigated areas in Tunisia is the result of morphology, organization and operation of agricultural policies implemented since independence, aimed at optimizing the exploitation of the best soils and natural resources, particularly water and productive crop intensification. The sustainability of the landscape of public irrigated areas has a strong bonding with the resources of irrigation water and their states of management. The scarcity of irrigation water due to drought generates profound changes in many public irrigated areas as Chott-Mariem and Mornag, like standpoint operating (decrease of production) and land occupation (transformation of agricultural land to urban land). An investigation was carried out with farmers, leaders and policy makers, which the result was a range of measures and recommendations to promote sustainability of agricultural landscape.